Use of the Statistical Comparison Method in a Company's Financial Status Analysis - Mackevičius, Jonas; Tamulevičienė, Daiva; Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2019)
General economic, mathematical and heuristic study methods were used when analyzing the financial status of companies. In practice, the comparison method is the most widely applied one of all the general economic research methods. When it is applied, the actual indicators (absolute and relative) are compared to the ones planned inside the company; the indicators of the company are compared with the average ones of the industry or the best ones of other companies; indicators of different periods are compared. However, until now, the comparison method has barely been applied in practice using the averages of certain indicators and especially the multidimensional ones. The aim of the article is to develop a methodology for applying the statistical comparison method based on the calculation and evaluation of the multidimensional average. For achievement of the aim were used research methods: analysis of scientific literature, information collection, aggregation, detailing and summarizing. The article analyzes the significance, advantages and disadvantages of the traditional comparison method. The methodology for the comparison method based on the calculation of the multidimensional average and their comparison is proposed in the article. A concrete example of how to apply the comparison method using the multidimensional average calculation method to assess the financial position of companies is provided.